Perioperative management of total hip arthroplasty in hemophilia A following gene therapy - Yanyan Shao; Chuanlong Wu; Wei Liu; Yu Liu; Qiulan Ding; Wenman Wu; Xuefeng Wang; Lei Zhang; Chuan He; Jing Dai (Haematologica)
Not available.